Border Harms and Everyday Violence. The Lived Experiences of Border Crossers in Lesvos Island, Greece - Iliadou, Evgenia (2019)
In 2015, Lesvos a Greek Island located at the North-Eastern edge of the Aegean Sea at the borders with Turkey became an important gate for border crossers who were fleeing persecution, wars, conflicts, authoritarian regimes and violence. During 2015 over 800,000 border crossers arrived via the Aegean Sea and Turkey into Greece and out of them approximately 500,000 arrived via Lesvos. Lesvos suddenly became the epicentre of what is predominantly referred to as the refugee crisis. The overwhelming arrivals of people seeking international protection and the mainstream discourses by the media and policy makers created a theatrical border spectacle full of suffering, misery and death. Although, Greece and Lesvos has been an important gate for unauthorised border crossers since the 1990s, it was only after the death of Alan Kurdi –a Syrian border crosser child, whose body was washed ashore at Turkey’s coast- that shocked and sensitised the public opinion and the EU policy makers. Even though policy makers expressed their “deep concerns” for the increased death toll of border crossers, in the name of protection of human lives and public order enforced a strengthened militarised thanatopolitical border regime. This thesis is an ethnographic study which explores the multiple, multilayered border-related harms and everyday violence border crossers experience while seeking sanctuary in Europe. Having Lesvos as a case study this research aims to document the collateral casualties in human cost of the monolithic and cruel EU border regime and the politics of deterrence. The rationale of the thesis rests on the idea that violence, abjection, spatial and temporal confinements, stuckedness and deaths border crossers experience in Lesvos, and other EU countries are neither random, unforeseen, unpreventable “tragic” events nor accidents; they are instead an outcome of the continuum of multiple political decisions being enforced in time and space since the 1985 Schengen Agreement. By deploying ethnography with auto-ethnographical evocative narratives in the form of Vignettes this thesis examines the continuum of violence in time and space and its harmful long-term impacts upon border crossers’ lives